2019
DOI: 10.1097/gox.0000000000002541
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Temporal Artery Biopsy at a UK Tertiary Plastic Surgery Unit

Abstract: Background: Guidelines recommend temporal artery biopsy (TAB) for patients suspected of having giant cell arteritis (GCA). We evaluated the impact of TAB on the diagnosis and management of patients with suspected GCA at a tertiary plastic surgery unit. Methods: A retrospective review of all TAB procedures performed at our centre over 7 years was performed. One hundred and one patients were included in the study. Patients were classified into 3 diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…We also found that reopening surgical services required arriving at a shared understanding of the role of temporal artery biopsies among everybody involved in making decisions on how to reopen services. The surgical literature might be interpreted as suggesting that giant cell arteritis can be diagnosed with the 1990 American College of Rheumatology (ACR) classification criteria, 13 , 14 , 15 , 16 , 17 a view that implies that a negative temporal artery biopsy has no diagnostic use, or that there is minimal value in doing a biopsy after a few weeks of steroid therapy because of false negatives. 15 In contrast, the rheumatology and ophthalmology literature suggests that the 1990 ACR classification criteria are not suitable for clinical diagnosis of giant cell arteritis.…”
Section: Presentation Recognition Referral and Diagnosis Of Giant mentioning
confidence: 99%
“…We also found that reopening surgical services required arriving at a shared understanding of the role of temporal artery biopsies among everybody involved in making decisions on how to reopen services. The surgical literature might be interpreted as suggesting that giant cell arteritis can be diagnosed with the 1990 American College of Rheumatology (ACR) classification criteria, 13 , 14 , 15 , 16 , 17 a view that implies that a negative temporal artery biopsy has no diagnostic use, or that there is minimal value in doing a biopsy after a few weeks of steroid therapy because of false negatives. 15 In contrast, the rheumatology and ophthalmology literature suggests that the 1990 ACR classification criteria are not suitable for clinical diagnosis of giant cell arteritis.…”
Section: Presentation Recognition Referral and Diagnosis Of Giant mentioning
confidence: 99%
“…Seven studies 11,12,14,15,17,19,20 reported on both positive and negative TAB prebiopsy steroid duration, and one study 13 reported on only the TAB+ group. Post-biopsy steroid commencement was specifically stated in seven studies, [10][11][12][13][14]16,18 with three studies 10,14,18 commenting on both TAB positive and negative groups.…”
Section: Steroid Use Was Impacted By Tab Resultsmentioning
confidence: 99%
“…In total, five studies commented on surgical complications. Four studies 15 , 16 , 18 , 20 reported on the wrong tissue being sampled, while Cristaudo et al 1 reported one facial nerve injury. There was no reporting on hematoma, wound healing complications, or alopecia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations